Comparative Analysis of Jailed Balloon and Jailed Wire Techniques for Side Branch Protection in Coronary Bifurcation PCI: A Prospective Study - Waqas Ahmed, Hamid Ali Shah, Zohaib Ahmad, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: To compare the effectiveness of the jailed balloon technique versus the jailed wire technique in preventing side branch occlusion during bifurcation PCI. Methodology: A prospective comparative study was conducted at AFIC NIHD, Rawalpindi, from May 2023 to October 2023 enrolling 72 patients with significant coronary bifurcation lesions. Patients were equally divided into two groups: Group A (jailed balloon technique) and Group B (jailed wire technique). Baseline demographics, clinical presentation, angiographic characteristics, and procedural data were recorded. The primary outcome was the incidence of SBO after main vessel stenting, while secondary outcomes included side branch TIMI flow, need for rewiring, bailout stenting, and in-hospital major adverse cardiac events (MACE). Results: The mean age of participants was 60.1 ± 8.0 years, with a male predominance (76.4%). Baseline characteristics and lesion morphology were comparable between groups. SBO occurred in 5.6% of patients in Group A versus 22.2% in Group B (p=0.04). The need for side branch rewiring was lower in the jailed balloon group (8.3% vs. 25.0%, p=0.05). No significant difference was observed in periprocedural MI, in-hospital MACE, or bleeding events. Conclusion: The jailed balloon technique demonstrated superior protection of the side branch compared with the jailed wire technique, significantly reducing SBO and procedural complexity without increasing adverse events. This technique may be considered the preferred strategy for single-stent bifurcation PCI in suitable patients. Keywords: Coronary bifurcation lesions, Jailed balloon technique, Jailed wire technique, Side branch occlusion, Percutaneous coronary intervention (PCI)